THE “SCHOOL-MACHINE” THROUGH THE ARCHITECTURE MAGAZINES OF THE SIXTIES AND SEVENTIES: Received: 03rd June 2021; Revised: 05th November 2021, 11th November 2021, 31st January 2022; Accepted: 31st January 2022 - Martinazzo, Francesco (MATTER: International Journal of Science and Technology, 2022)
If we retrace the fundamental stages of the history of education, we notice how school, with “Distance Teaching”, seems to be in a kind of zero degrees of education. From the one-to-one relationship of Socrates with his students, we find ourselves today in a situation similar to the first, but in which the teacher and the pupil disappear from the physical space, to appear on the screen of a technological device. However, much of the student's education passes through the school space as an educational environment, both because of the social relationships it brings with it and because of the space's intrinsic capacity to encourage or hinder well-being. The research reflects on the concept of "school-machine", born in the sixties, where technology is not applied a posteriori to the building, but the building itself is conceived as a technological-typological device at the service of learning. To clarify this definition, school projects have been catalogued by methodically scanning the international architecture magazines of the 1960s and 1970s. These examples want to be presented to stimulate a reflection on the way the school can be rethought for the post-COVID era as strategic infrastructure, illuminating the many analogies between that season and ours.